Genealogy of the Raja Alam Pagaruyung Dynasty in Kitab Salasilah Rajo-Rajo di Minangkabau (1336-1825) - Kurnia, Sultan; Permana, Zera; Soares, Ghio V. D; Suparmi, Suparmi; Aldrat, Hendri; Khudri, Khudri; Asmara, Adhiko E (Regalia Institute, 2023)
Studies on the history and genealogy of the Raja Alam Pagaruyung are still limited, one of the reasons is the lack of written sources. Previous studies have only revealed several kings in Pagaruyung, such as Adityawarman (14th century AD), Sultan Ahmadsyah, and Gagar Alam (17th - 18th century AD). Therefore, this study aimed to explain the history and genealogy of the Raja Alam Pagaruyung from the 14th century to the 19th century AD. This study used historical research methods: heuristics, source criticism, interpretation, and historical writing. The two main sources are a photocopy and the translation book of Kitab Salasilah Rajo-Rajo di Minangkabau manuscript. The results of this study showed that the Raja Alam Pagaruyung Dynasty was the descendant of previous king dynasties, namely the dynasty of kings in Bukit Siguntang (Palembang), Sumpur Sireno Puro, Malayu Tapi Air Jambi, and Ranah Tiga Laras (Dharmasraya). The existence of Raja Alam is related to Dewang Palakama Raja Indra Dewawana (Adityawarman) as Raja Undang in the Rajo Tigo Selo concept (1336-1376). Later, the term Raja Undang was changed to Raja Alam by Dewang Pandan Putowano as the fourth king (1420 – 1457). The first 12 Kings of Alam Pagaruyung reigned at Balai Gudam, but since the Yamtuan Bakilap Alam period (1543), they moved to Balai Janggo.